A competitividade da cadeia de valor global da carne de frango: o caso da Mais Frango Miraguaí Ltda - Miritz, Luciane Dittgen (2016)
The world economy has changed dramatically over the last three decades in the twentieth century, especially in the areas of international trade and industrial organization. Within this new global configuration, markets have expanded and affected the industries organization and the value chain of companies, requiring new policies from countries to deal with changes in international environment. This thesis aims to analyze the Global Value Chain (GVC) of poultry meat produced by the agribusiness Mais Frango Miraguaí LTDA, in Rio Grande do Sul/Brazil, and to determine, from this company, the origin of their export competitiveness. Thus, the GVC of agribusiness Mais Frango Miraguaí Ltda was described; the stimuli for poultry breeders and for the slaugterhouse in GVC were determined; the competitive advantage of agribusiness in the production of poultry meat to international market was evaluated; and the effects of policies over financial costs in GVC were identified. For this, were analyzed the agribusiness GVC, through interviews with company managers, technical assistance and farmers, and data were collected considering production costs, referring to September 2015. The coordinator link of GVC is the slaugterhouse, adding to this upstream farmers and other input suppliers, and downstream the consumer market, domestic and external market. The competitiveness of the chain was analyzed by the Policy Analysis Matrix (PAM), which has proven its efficiency with Shawarma product produced (breast and boneless drumstick in a whole piece). The GVC is competitive, since it presents private prices and profits, it has comparative advantage, and the social profits are also positive, even the chain being aggravated by taxes and social charges. It was found that the captive coordination, through the existing integration agreements between the slaugterhouse and the producer, the use of high genetic standard, strict sanitary management, efficient management and product value added, are the main competitive elements of this chain.